Mapping Second Chromosome Mutations to Defined Genomic Regions in Drosophila melanogaster. Issue 1 (1st January 2018) - Kahsai, Lily; Cook, Kevin R
Abstract: Hundreds of Drosophila melanogaster stocks are currently maintained at the Bloomington Drosophila Stock Center with mutations that have not been associated with sequence-defined genes. They have been preserved because they have interesting loss-of-function phenotypes. The experimental value of these mutations would be increased by tying them to specific genomic intervals so that geneticists can more easily associate them with annotated genes. Here, we report the mapping of 85 second chromosome complementation groups in the Bloomington collection to specific, small clusters of contiguous genes or individual genes in the sequenced genome. This information should prove valuable to Drosophila geneticists interested in processes associated with particular phenotypes and those searching for mutations affecting specific sequence-defined genes.